Experimental study of complex currents (three-dimensional jet and body wake) - Toleuov, G.; Issatayev, M.S.; Seidulla, Zh.K. (Ye.A.Buketov Karaganda State University Publishing house, 2017)
The studies of the heat transfer of a finite size streamlined surface were conducted. The experimental results of the investigation of the large-scale formations development in complex currents (body wake) are shown. The general patterns (analogy) of such flows with a three-dimensional free jet are finding. The distribution of velocity fields in vortices and vortex clusters in turbulent free three-dimensional jets had been identified as one of the varieties of complex jet streams. A comparison of varieties of complex jet streams is given.
Keywords: autocorrelation function; vortex; large-scale vortices; body wake; three-dimensional free jet; vortex cluster; complex jet stream